Discrete mathematical structures - Kolman, Bernard ...[ et al ] (Pearson Education, 2006)
Discrete mathematical structures / Kolman, Bernard ...[ et al ]. -- New Delhi: Pearson Education, 2006 511.3 K81 No. of Copies : 1